PENGARUH BUDGETARY GOAL CHARACTERISTICS TERHADAP KINERJA MANAJERIAL DIMODERASI OLEH SISTEM PENGENDALIAN MANAJEMEN (Studi Empiris Perusahaan Manufaktur Berskala Besar di Kota Cilegon) Larissa Anditha Gestari - Gestariana, Larissa Anditha; Bastian, Elvin (Pascasarjana Universitas Sultan Ageng Tirtayas, 2018)
The performance of managers will be said to be effective if the organizational goals set forth in thebudget can meet the five indicators in the Budgetary Goal Characteristics, including budgetaryparticipation, budget clarity, budgetary evaluation,budgetary feedback, and budget goal difficulty.However, the relationship between Budgetary Goal Characteristics to Managerial Performance will be stronger or vice versa become weaker with other factors involved in the budget that is Management Control System. Therefore, this research is important to measure the performance budgeting of largescale manufacturing industry, because the procedures and management control system in manufacturing companies is more complex. The sample in this research is a manufacturing company with large scale metal business in Cilegon City. Data collection method in this study is the primary data through the distribution of questionnaires. The data is processed by using SPSS program version 22.0 with multiple linear regression approach and Moderated Regression Analysis (MRA) test. The results show that the five components of Budgetary Goal Characteristics have a positive effect on managerial performance and overall the Management Control System is able to strengthen the relationship between Budgetary Goal Characteristics to Managerial Performance. Keywords: Budgetary Goal Characteristics, Management Control Systems and Managerial Performance